Remote, Inc. : How to Thrive at Work . . . Wherever You Are - Pozen, Robert C.; Samuel, Alexandra (United Kingdom HarperCollins, 2021)
Thinking of yourself as Remote, Inc. means you have the responsibility and accountability of a business owner, but also the flexibility and independence. It means thinking in terms of outcomes and final products, instead of schedules and billable hours. This book aims to provide you with practical strategies and tools that will make you more productive as a remote worker, and more valuable to your employer or clients.
mck23/08/22
Loans
Keywords: BUSINESS & ECONOMICS: Personal Success; BUSINESS & ECONOMICS: Careers / General; SELF-HELP: Self-Management / Time Management